Normal pressure hydrocephalus associated with chronic alpha interferon treatment: A case report - (:unkn) unknown (My University, 2000)
Chronic α-interferon use has been reported to cause a variety of neurotoxic side effects. This case summary suggests the possibility of a new neurotoxic side effect of normal pressure hydrocephalus following chronic α-interferon use.
Keywords: Alpha interferon; Normal pressure hydrocephalus